PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASA KERJA DAN KOMITMEN ORGANISASIONAL (STUDI PADA KARYAWAN GENERASI Y SEKTOR PERBANKAN SE-KOTA MATARAM) - mohammad najib rodhi (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research aimed to analyze and determine the significant effect of compensation and work environment on the work satisfaction and organisational commitment of employees of Y generation working in banking sector in the city of Mataram, Indonesia. The population of this explanatory research are all employees including those of Y generation, all of whose number is unknown exactly. The data were collected with survey method from samples selected through nonprobability sampling which was limited by criteria of respondents (purposive sampling). The questionnaires were distributed online. 182 respondents participated in this research. The data then were processed with structured equation modeling (SEM) using AMOS program version 20.0. Based on the data processing with the SEM, it showed that compensation had positive and significant effect on organisational commitment, work environment had positive effect on organisational commitment, work satisfation had positive effect on organisational commitment, compensation had positive effect on work satisfaction, and work environment had positive effect on work satisfaction. Keywords : compensation, work environment, work satisfaction,  organizational commitment, and Y generation